2021
DOI: 10.2991/assehr.k.210805.140
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Advertising in Tiktok Social Media and Beauty Product Image on Consumer Purchase Decisions

Abstract: The use of TikTok's social media, which is increasingly popular with young people, has made marketers interested in advertising to market beauty products. However, the problem is that it is not easy to attract the attention of the audience to focus on one product on TikTok social media, adding that a less positive image of beauty products can result in the audience not making purchase decisions. The research objective was to determine the effect of advertisements on TikTok social media and the image of beauty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…TikTok memudahkan interaksi antara pemirsa dan penjual dalam sesi live. Pemasaran melalui TikTok berpengaruh terhadap keputusan pembelian, hal ini dibuktikan oleh penelitian (Setianingsih & Aziz, 2022), (Mettasatya Afrilia, 2018), (Darmatama & Erdiansyah, 2021). Iklan, kredibilitas, dan hiburan berpengaruh positif terhadap sikap konsumen terhadap iklan; sehingga menghasilkan korelasi positif antara sikap terhadap periklanan terhadap niat membeli.…”
Section: Hasil Dan Pembahasanunclassified
See 1 more Smart Citation
“…TikTok memudahkan interaksi antara pemirsa dan penjual dalam sesi live. Pemasaran melalui TikTok berpengaruh terhadap keputusan pembelian, hal ini dibuktikan oleh penelitian (Setianingsih & Aziz, 2022), (Mettasatya Afrilia, 2018), (Darmatama & Erdiansyah, 2021). Iklan, kredibilitas, dan hiburan berpengaruh positif terhadap sikap konsumen terhadap iklan; sehingga menghasilkan korelasi positif antara sikap terhadap periklanan terhadap niat membeli.…”
Section: Hasil Dan Pembahasanunclassified
“…Dengan TikTok memudahkan interaksi antara viewer dan seller. Marketing melalui TikTok berpengaruh terhadap keputusan pembelian hal ini dibuktikan oleh penelitian (Julianti,2023), (Darmatama & Erdiansyah, 2021), (Mettasatya Afrilia, 2018) (Mussa, 2023). TikTok marketing berpengaruh terhadap kesadaran merek (Aubrey Gesmundo et al, 2022).…”
Section: Sosialisasi Digital Marketing Melalui Tiktok Marketingunclassified
“…The findings demonstrated that social media advertising on TikTok and the perception of beauty products collectively had a considerable impact on customer purchasing decisions. The most significant factor influencing customer purchasing decisions is product image (Darmatama & Erdiansyah, 2021). In his research, he has been researching about one's behaviour.…”
Section: Problem Statementmentioning
confidence: 99%
“…In previous research conducted by Darmatama & Erdiansyah (2021), which discusses about influence of advertising on TikTok social media on purchase decisions, shows that there is a strong and significant influence between advertisement on TikTok towards purchasing decisions on the beauty products offered. Other research conducted by Nur Ratri (2021) shows that, there is a significant and positive correlation between advertisements on video content and the hashtag #Shopeehaul on TikTok on the consumer behavior of the millennial generation.…”
Section: Introductionmentioning
confidence: 99%